The importance of the division of the countryside in stimulating regional development - Kladnik, Drago (Acta geographica Slovenica, 2003)
In this paper, the authors divide Slovenia's countryside on the basis of selected indicators combined in eight different content complexes, which they call "partial syntheses": Natural Limitation Factors, Land and Agricultural Systems, Property Conditions, Population Characteristics, Characteristics of Economic Efficiency, Personal Infrastructure, Frontier Status, and Agricultural Burdening of the Environment. The partial syntheses are the basis of an integral synthesis with five distinct levels of countryside development. In the second part of paper, the importance of the division of the countryside is presented from the viewpoint of providing diverse forms of assistance to ensure its coordinated development, as well as from the viewpoint of monitoring indicators of deviations from the desired impacts of regional development to which the term "regional disparities" refers.
Keywords: Slovenia; Slovenija; podeželje; rural area; tipizacija; regionalizacija; regionalni razvoj